Construction of Notable Sums - Quispe Pucuhuayla, Jorge (2023)
This article presents a strategy to calculate the sum of numbers natural ones each raised to the fourth, the fifth, the sixth, etc. Furthermore, it is shown that. The proposed strategy can be used to calculate the sum of natural numbers each raised to any natural power n.